2017
DOI: 10.1155/2017/5820405
|View full text |Cite
|
Sign up to set email alerts
|

Bletilla striata Micron Particles Function as a Hemostatic Agent by Promoting Rapid Blood Aggregation

Abstract: The human body cannot control blood loss without treatment. Available hemostatic agents are ineffective at treating cases of severe bleeding and are expensive or raise safety concerns. Bletilla striata serve as an inexpensive, natural, and promising alternative. However, no detailed studies on its hemostatic approach have been performed. The aim of this study was to examine the hemostatic effects of B. striata Micron Particles (BSMPs) and their hemostatic mechanisms. We prepared and characterized BSMPs of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Modern pharmacology research has further proven that B. striata fights against bacteria (Li et al 2014;Guo et al 2016;Jiang et al 2019), influenza A virus (Shi et al 2017), fibrosis (Wang et al 2014) and tumorigenesis (Zhan et al 2014) and promotes wound (Diao et al 2008;Luo et al 2010) and oral ulcer healing (Liao et al 2019). Additionally, B. striata is used as a hemostatic agent since it promotes rapid blood coagulation (Hung and Wu 2016;Zhang et al 2017). "Yunnan Bai Yao", made mainly from B. striata, has been popular for wound healing for more than a hundred years.…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacology research has further proven that B. striata fights against bacteria (Li et al 2014;Guo et al 2016;Jiang et al 2019), influenza A virus (Shi et al 2017), fibrosis (Wang et al 2014) and tumorigenesis (Zhan et al 2014) and promotes wound (Diao et al 2008;Luo et al 2010) and oral ulcer healing (Liao et al 2019). Additionally, B. striata is used as a hemostatic agent since it promotes rapid blood coagulation (Hung and Wu 2016;Zhang et al 2017). "Yunnan Bai Yao", made mainly from B. striata, has been popular for wound healing for more than a hundred years.…”
Section: Introductionmentioning
confidence: 99%
“…f. (Orchidaceae) has been widely used as a common medicinal plant and horticulture specimen in many countries for several centuries. The pseudobulbs of this traditional Chinese medicinal (TCM) herb have various medicinal properties, including hemostatic [ 1 ], anti-inflammatory, and antibacterial [ 2 ] activities, as well as the ability to reduce swelling and promote tissue regeneration [ 3 ]. In addition, previous studies also demonstrated that B .…”
Section: Introductionmentioning
confidence: 99%
“…(2) Bletilla striata particles spur hemostatic modes of action by forming a visible particle/blood aggregate as a physical barrier that gives rise to hemostasis. The hemostatic results of 350-250 μm particles were found to be the most efficient [27]. (3) Bletilla striata has the activity anti-inflammatory.…”
Section: Discussionmentioning
confidence: 99%